Du trimorphe aux frontières quasi topologiques - Jean-Pierre Desclés (Ateliers d'Anthropologie)
Topology is used in linguistics for semantic, lexical and grammatical descriptions. However, classical topology, with its notion of the limit, is insufficient. Therefore, to describe numerous semantic oppositions (such as “again” / “not again”, “already” / “already no longer”), one must invoke “thick boundaries”—internal and external boundaries. Navigating topological places (temporal, spatial, spatio-temporal, notional) means crossing these different boundaries. In ethnology, initiation and ritual enactment situations can be described with the help of quasi-topological schemas.